PENGARUH PENDIDIKAN, JUMLAH PENDUDUK DAN PDRB TERHADAP KEMISKINAN DI PROVINSI KALIMANTAN BARAT - Bahrain Mawarid Rinaldy (2022)
Poverty is a fundamental problem that occurs in various parts of the world, especially in developing countries. Therefore, appropriate policies are needed for each country so that the problem of poverty can be resolved properly by increasing the welfare of the community evenly. The purpose of this study was to determine the effect of the average length of school, number of population and GRDP on poverty in West Kalimantan Province. This study took samples using the saturated sampling technique in 14 regencies/cities within a period of 6 years starting from 2015-2020, so the sample in this study amounted to 84 data whose sources were obtained from the Central Statistics Agency (BPS). This study uses panel data regression analysis through E-views 10 software as a data processing instrument. The results of this study show that partially the average length of school and number of population do not show a significant effect on poverty, while GRDP shows a significant positive effect on poverty. Simultaneously, the results of this study show that the average length of school, population and GRDP have an effect on poverty.